ELISA-Based Crossmatching Allowing the Detection of Emerging Donor-Specific Anti-HLA Antibodies through the Use of Stored Donors' Cell Lysates. (8th November 2015) - Schlaf, G.; Stöhr, K.; Rothhoff, A.; Altermann, W.
Abstract : About forty years ago the complement-dependent crossmatch assay (CDC-CM) was developed as standard procedure in order to select recipients without donor-specific antibodies directed against human leukocyte antigens of their given donors since the negative outcome of pretransplant crossmatching represents one of the most important requirements for a successful kidney graft survival. However, as a functional assay the CDC-CM strongly depends on the availability of donors' isolated lymphocytes and in particular on their vitality highly limiting its applicability for recipients treated with special drugs and therapeutic antibodies or suffering from underlying autoimmune diseases. In the great majority of these cases ELISA-based crossmatching has been demonstrated to be an adequate alternative procedure nevertheless leading to valid results. With these case reports we show for the first time that ELISA-based crossmatching is suitable to demonstrate the upcoming donor-specific anti-HLA antibodies as a consequence of allografting using deep-frozen deceased donor's material such as blood or spleen detergent lysate. Thus, this ELISA-based procedure first provides the option to routinely perform crossmatching using stored material of deceased donors in order to substitute or at least to complement virtual crossmatching, that is, the comparison of the recipients' anti-HLA antibody specificities with the donors' historically identified HLA types.